Zmiany poziomu kortyzolu i testosteronu we krwi u sprinterów po sprintach na dystansie 100 m w czasie waznych zawodów - Obminski, Z.; Lerczak, K. (Medycyna sportowa, 2001)
The aim of the study was to determine cortisol and testosterone levels in 100 m-sprinters participating in an international competition. Four male and 4 female sprinters ran 100 m in the afternoon, and after 90 min ran relay 4 x 100 m. Despite afternoon hours, the pre-start cortisol levels were high, and higher (p = 0,06) before team relay than before single runs. The post-run cortisol was significantly (p < 0,01) higher than the pre-start one. No significant changes in testosterone levels were noted in either sex.